Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.24171/j.phrp.2018.9.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Practice of Road Safety among Medical Students, Mansoura, Egypt

Abstract: ObjectivesTo assess the knowledge and attitude of medical students towards road safety and to determine their driving behavior and its relation to different related factors.MethodsThis cross-sectional study involved 480 medical students at Mansoura University, Egypt. A self-administered questionnaire was used to collect student personal data, knowledge about road safety, attitude towards road safety, and driving practices.ResultsMore than 40% of students experienced an injury in the previous year, mainly as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In this study, the prevalence of road traffic injuries as reported by the study participants in the past 2 years was 30.4%. In a study done by Helal et al .,[ 13 ] 40% of the participants had sustained injuries in the past year, out of which the majority had experienced injuries as pedestrians. In one another study done by Balaji et al .,[ 14 ] 41.32% of the students had experienced RTA.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of road traffic injuries as reported by the study participants in the past 2 years was 30.4%. In a study done by Helal et al .,[ 13 ] 40% of the participants had sustained injuries in the past year, out of which the majority had experienced injuries as pedestrians. In one another study done by Balaji et al .,[ 14 ] 41.32% of the students had experienced RTA.…”
Section: Discussionmentioning
confidence: 99%
“…Medical science students make up a significant portion of the young population of any society. In their capacity to affect the health status of communities in the future, they must increase young people's awareness about various healthy behaviors, such as road safety, and also be responsible for emergency care 17 …”
Section: Introductionmentioning
confidence: 99%
“…In their capacity to affect the health status of communities in the future, they must increase young people's awareness about various healthy behaviors, such as road safety, and also be responsible for emergency care. 17 Traffic accidents in the world, particularly in Iran, are a major issue that affects society's health. Also, considering the high statistics Therefore, according to the following formula, the sample size was estimated to be 217 students.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on the factors influencing personal behavior for accident prevention, and have indicated that gender, age, driving experience and marital status etc. are significantly associated with safe driving (Uttra et al, 2020;Aden, 2019;Helal, et al, 2018;Zhang, et al, 2013). Risky behavior is a direct cause of road accidents, such as drunk driving, speeding, mobile phone use while driving, and motorbike rider not wearing a helmet, etc.…”
Section: Introductionmentioning
confidence: 99%